Penanaman sikap sosial melalui pembelajaran IPS pada siswa kelas 7 di MTs al-Ma’arif 03 Singosari - Imani, Raniah Oktariza (Maliki Interdisciplinary Journal, 2024)
In an era where access to information is increasingly easy through the internet and social media, dismissive attitudes towards teachers and schools have become increasingly prominent among students. This reflects changing culture and values among the younger generation, who often have less appreciation for the role of teachers and the importance of formal education. One of the schools facing this challenge is MTS Al-Ma'arif 03 Singosari, which is in a village where the majority of people consider education not that important. Therefore, it is necessary to conduct research to understand how social studies learning can help change the social attitudes of grade 7 students at this school. The aim of this research is to describe the process of instilling social attitudes through social studies learning in grade 7 students at MTS Al-Ma'arif 03 Singosari. This study used descriptive qualitative method. This approach allows researchers to gain an in-depth understanding of how social studies learning at the school contributes to shaping students' social attitudes. Through direct classroom observations, interviews with teachers and students, as well as analysis of social studies learning materials, researchers describe in detail the learning strategies used, interactions between teachers and students, and students' responses to the learning. The results of the social studies learning process at MTS Al-Ma'arif 03 Singosari emphasize the integration of social attitudes and values as an integral part of the curriculum and their teaching approach to grade 7 students. Teachers at this school consistently implement learning models that encourage social interaction. healthy and development of positive attitudes. The learning process not only teaches theoretical concepts about social sciences, but also helps students interpret their daily lives better. The impact of social studies learning on cultivating students' social attitudes is very positive, with students becoming more concerned about their social environment and ready to contribute positively to society. Therefore, social studies learning at MTS Al-Ma'arif 03 Singosari has an important role in shaping the character and social attitudes of grade 7 students.